2018
DOI: 10.3198/jpr2017.10.0070crgs
|View full text |Cite
|
Sign up to set email alerts
|

Registration of the Barley Transposon‐Tagged Population II: Sixty‐One Lines Each Characterized for Ds Insertion Sites

Abstract: The USDA-ARS has developed and released a transposontagging barley (Hordeum vulgare L.) population comprising 61 lines: TNPs Each line is homozygous for a single modiied Ds element encoding bar (Ds-bar) insertion at a diferent genomic location, except for TNP 120, which has two insertions. The ~3.6 kb Ds-bar element is a modiied maize (Zea mays L.) Dissociation (Ds) element containing a bar expression cassette. Two of lines (TNP 32B and TNP 48) derive from primary Ds (PDS) transpositions resulting from biolist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…PSTOL1 proteins possess structural features of wall-associated kinase (WAK) proteins such as Ser/Thr kinase, transmembrane, and extracellular domains important for their functionality in the cell wall (He et al, 1999 ). Analysis of single-copy Ds transposon mutant repository of barley (Singh et al, 2006 , 2012 ; Bregitzer et al, 2019 ) revealed that WAK proteins are implicated in the root growth of barley (Kaur et al, 2013 ; Tripathi et al, 2021 ), and that they are potentially new gene candidates for P starvation tolerance.…”
Section: Phosphorus Use Efficiencymentioning
confidence: 99%
“…PSTOL1 proteins possess structural features of wall-associated kinase (WAK) proteins such as Ser/Thr kinase, transmembrane, and extracellular domains important for their functionality in the cell wall (He et al, 1999 ). Analysis of single-copy Ds transposon mutant repository of barley (Singh et al, 2006 , 2012 ; Bregitzer et al, 2019 ) revealed that WAK proteins are implicated in the root growth of barley (Kaur et al, 2013 ; Tripathi et al, 2021 ), and that they are potentially new gene candidates for P starvation tolerance.…”
Section: Phosphorus Use Efficiencymentioning
confidence: 99%
“…Previous studies have suggested that Ac/Ds can insert into gene-rich regions and alter the expression of genes or the genome through the formation of unstable insertion alleles, stable derivatives, or excision alleles. [23][24][25] Until now, Ac/Ds transposons have been shown to be effective in approximately 20 plant species and have become the most widely used TEs for gene tagging and functional genomics studies in plants. For example, Carter et al 25 produced activation-tagged and knockout mutants in the processing of tomato cultivar M82 using the Ac/Ds system and agrobacterium-mediated method.…”
mentioning
confidence: 99%